2007
DOI: 10.1160/th07-01-0039
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and fibrin induce synthesis of proinflammatory cytokines from isolated peripheral blood mononuclear cells

Abstract: Fibrinogen in plasma includes three main fractions; high-molecular-weight (HMW)-fibrinogen, low-molecular-weight (LMW)-fibrinogen, and very-low-molecular-weight (LMW')-fibrinogen. During acute-phase conditions, plasma fibrinogen levels and the HMW-/LMW-fibrinogen ratio increase rapidly due to increased synthesis of HMW-fibrinogen. The consequences of elevated plasma fibrinogen levels and local deposition of fibrin in inflammatory tissues observed during acute-phase conditions are not clear. We wanted to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 39 publications
0
60
0
1
Order By: Relevance
“…It has been reported that fibrinogen plays an important role on the process of inflammation, promoting proinflammatory cytokines synthesis in peripheral blood inflammatory environment 20,21. An interesting animal experiment showed that fibrinogen might be a critical factor of the metastatic potential in lung carcinoma and melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fibrinogen plays an important role on the process of inflammation, promoting proinflammatory cytokines synthesis in peripheral blood inflammatory environment 20,21. An interesting animal experiment showed that fibrinogen might be a critical factor of the metastatic potential in lung carcinoma and melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is also one of the important coagulation parameters, which is synthesized effectively in the liver and can be converted to fibrin by thrombin during the coagulation cascade [12]. Fibrinogen usually functions as an acute-phase protein with a normal concentration of 2 to 4 g/L in the plasma, increasing in level in response to most forms of wound healing, infection, inflammation or generation of tumor stroma [13-15]. It is increasingly recognized that basal fibrinogen levels can be used as an independent prognostic parameter in lung cancer, as well as pancreatic cancer, gastric cancer, colon cancer, esophageal cancer, gynecological malignancies and renal cancer [16-27].…”
Section: Introductionmentioning
confidence: 99%
“…Even before extravasation into the perivascular space, increased fibrinogen and its derivative peptides in the blood induce blood mononuclear cells to synthesize pro-inflammatory cytokines, such as TNF-α, IL-6 and IL-1β[32,33], activate neutrophils[34], mediate leukocyte adhesion to the vascular endothelium[35,36], and increase leukocyte migration[36], notably leukocyte transendothelial migration[37]. Fibrinogen can bind to both endothelial cells and platelets increasing vascular permeability and causing their local aggregation, as well as inducing fibrin and thrombin production[6,38,39] permitting fibrinogen, fibrin, thrombin, and other plasma constituents to escape the vasculature[40].…”
Section: Discussionmentioning
confidence: 99%